Prescribed‐Fire Effects on an Aquatic Community of a Southwest Montane Grassland System. (3rd October 2013) - Caldwell, Colleen A.; Jacobi, Gerald Z.; Anderson, Michael C.; Parmenter, Robert R.; McGann, Jeanine; Gould, William R.; DuBey, Robert; Jacobi, M. Donna
Abstract: The use of prescription fire has long been recognized as a reliable management tool to suppress vegetative succession processes and to reduce fuel loading to prevent catastrophic wildfires, but very little attention has been paid to the effects on aquatic systems. A late‐fall prescribed burn was implemented to characterize effects on an aquatic community within a montane grassland system in north‐central New Mexico. The fire treatment was consistent with protocols of a managed burn except that the fire was allowed to burn through the riparian area to the treatment stream to replicate natural fire behavior. In addition to summer and fall preburn assessment of the treatment and reference stream, we characterized immediate postfire effects (within a week for macroinvertebrates and within 6 months for fish) and seasonal effects over a 2‐year period. Responses within the treatment stream were compared with an unburned reference stream adjacent to the prescription burn. During the burn, the diel range in air temperature increased by 5°C while diel range in water temperature did not change. Carbon–nitrogen ratios did not differ between treatment and reference streams, indicating the contribution of ash from the surrounding grassland was negligible. Although total taxa and species richness of aquatic macroinvertebrates were not altered, qualitative indices revealed departure from preburn condition due to loss of sensitive taxa (mayflies [order Ephemeroptera] and stoneflies [order Plecoptera]) and an increase in tolerant taxa (midges [order Chironomidae]) following the burn. Within 1 year of the burn, these attributes returned to preburn conditions. The density and recruitment of adult Brown Trout Salmo trutta did not differ between pre‐ and postburn collections, nor did fish condition differ. Fire is rarely truly replicated within a given study. Although our study represents one replication, the results will inform managers about the importance in timing (seasonality) of prescription burn and anticipated effects on aquatic communities. Received January 9, 2013; accepted June 27, 2013